2005
DOI: 10.4269/ajtmh.2005.72.103
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Toxocariasis in Northeastern Brazil Based on Serology Using Recombinant Toxocara Canis Antigen

Abstract: To evaluate the prevalence of toxocariasis in children in Jaboatão dos Guararapes, Pernambuco in northeastern Brazil, 215 serum samples were examined by an enzyme-linked immunosorbent assay (ELISA) using a recombinant Toxocara canis antigen. In the ELISA, 26 (12.1%) of 215 subjects were positive. In a dot-blot assay using 53 of 215 serum samples, the diagnostic results correlated with those obtained by the ELISA. Moreover, it has been confirmed that the recombinant T. canis antigen was highly specific for toxo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 28 publications
2
12
0
4
Order By: Relevance
“…The ELISA system applied for paragonimiasis in this study was much more sensitive for diagnosis than detection of eggs as already shown (Figure 2) [11]. As it has already been shown that the ELISA for toxocariasis in this study showed no cross-reactions with ascariasis patients in Asia and Latin America [20], [21], we consider that it is highly specific to toxocariasis. As children are the most risky population for toxocariasis and the prevalence of T. canis in dogs in Cameroon was very high [9], we expected that 61 persons (36.3%) were really exposed to eggs of Toxocara [22], [23].…”
Section: Resultssupporting
confidence: 71%
“…The ELISA system applied for paragonimiasis in this study was much more sensitive for diagnosis than detection of eggs as already shown (Figure 2) [11]. As it has already been shown that the ELISA for toxocariasis in this study showed no cross-reactions with ascariasis patients in Asia and Latin America [20], [21], we consider that it is highly specific to toxocariasis. As children are the most risky population for toxocariasis and the prevalence of T. canis in dogs in Cameroon was very high [9], we expected that 61 persons (36.3%) were really exposed to eggs of Toxocara [22], [23].…”
Section: Resultssupporting
confidence: 71%
“…By contrast, US seroprevalence rates are lower than reported for some middle income or developing countries, with rates of toxocariasis reaching 40% or higher in Indonesia and Brazil (Noordin et al 2005;De Andrade Lima Coelho et al 2005). Application of prevalence modeling to such settings may need to be sensitive to climatic and seasonal effects (e.g., Paquet-Durand et al 2007), as well as to major demographic variations (e.g., among aboriginal groups) (e.g., Fan et al 2004).…”
Section: Discussionmentioning
confidence: 79%
“…No Brasil, estudos soroepidemiológicos sobre toxocaríase humana mostraram variação na prevalência de 7 a 54,8% 13,16,33,42,55,[60][61][62][63][64][65][66] .…”
Section: Epidemiologiaunclassified